Agreement between methods for antimicrobial susceptibility to Mycobacterium tuberculosis strains isolated in Montería, Córdoba: mycobacteria growth indicator tube vs. proportion method. - Miranda, Jorge; Rios, Rodrigo; Mattar, Salim; Alvis, Nelson (Colombia Medica, 2008)
Objective: To evaluate the agreement of manual MGIT (mycobacteria growth indicator tube for antimicrobial susceptibility testing to isoniazid, rifampin, ethambutol and streptomycin) for susceptibility testing vs proportion method on Lowenstein-Jensen (PM) in Mycobacterium tuberculosis strains. Methods: A total of forty-five isolates of M. tuberculosis were tested for susceptibility to isoniazid (INH), rifampin (RMP), ethambutol (EMB), and streptomycin (SM). The strains were isolated in Montería, during 2003 and 2005. The agreement between the two assays mentioned was estimated by the Kappa test. Results: There were thirty-eight strains with identical results while 7 had discrepant results with both methods. The overall resistance to antituberculosis drugs were 33.3% y 31.1% for manual MGIT and PM, respectively. MDR was 5 (11.1%) by PM and 4 (8.8%) by manual MGIT. The agreement between MGIT AST and PM was 95.5% for all drug tested and overall kappa value 0.8374. Two discrepancies were found in each drug; with INH and RIF (one false resistant and one false susceptible). STR and EMB (two false susceptibles). Turnaround times were 5 to 8 days (median, 6.5 days) for MGIT and 20 to 25 days for MP. Conclusions: These preliminary data show a good level of agreement between manual MGIT AST SIRE and MP. Also MGIT is a rapid, easy and efficient method for the drug susceptibility testing of M. tuberculosis.